THE COUNCIL OF EUROPE’S CONTRIBUTIONS TO GLOBAL REGULATION OF ARTIFICIAL INTELLIGENCE. REVIEW OF COUNCIL OF EUROPE’S LEGAL INSTRUMENTS RELATING TO ARTIFICIAL INTELLIGENCE AND PARTICULAR STAKES IN THE AREA OF HEALTHCARE AND BIOMEDICINE - MENECEUR, Yannick; HIBBARD, Lee (MEDECINE LEGALE DROIT MEDICAL, 2025)
The Council of Europe has been involved in regulating the use of technologies, in particular those relating to computer systems and biomedical technologies, for a long time – the first international text on data protection dates back to 1981 and the one on biomedicine to 1997. The regulation of artificial intelligence is part of this dynamic, seeking a balance between soft law instruments and other, potentially binding instruments. The stakes for health and biomedicine merit special attention in view of numerous risks, such as the potentially profound transformation of the relationship between patients and doctors.